DEMOKRASI AGONISTIK DAN SPIRIT BARU PASCA-PILKADA - Jehalut, Ferdi (JAP UNWIRA, 2020)
Abstract The simultaneous general election of district heads in 270 regencies, municipalities and provinces in Indonesia in 2020 has ended. The end of the simultaneous general elections does not mean the end of competition, debate and discourse in democracy. A living democracy needs constant contestation, debate and discourse. That is the essence of the idea of agonistic democracy. The idea of agonistic democracy will be discussed in a sharp and comprehensive manner in this paper. Thus, the aim of this paper is to explain the concept of agonistic democracy. Furthermore, starting from the idea of agonistic democracy, the writer will show what spirit needs to be nurtured after the simultaneous regional elections that have just been held. The approach used in this paper is a speculative-analysis approach.